Measurement of the $\mathrm{t}\overline{{\mathrm{t}}}$ production cross section in the all-jets final state in pp collisions at $\sqrt{s}=8$ $\,\text {TeV}$ - CMS collaboration (2304 authors); Hollar, Jonathan; Calpas, Betty; Nayak, Aruna; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Di Francesco, Agostino; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Leonardo, Nuno; Lloret Iglesias, Lara; et al. (My University, 2016)
The cross section for $\mathrm{t}\overline{{\mathrm{t}}}$ production in the all-jets final state is measured in pp collisions at a centre-of-mass energy of 8  $\,\text {TeV}$ at the LHC with the CMS detector, in data corresponding to an integrated luminosity of 18.4  $\,\text {fb}^{-1}$ . The inclusive cross section is found to be $275.6 \pm 6.1 \,\text {(stat)} \pm 37.8 \,\text {(syst)} \pm 7.2 \,\text {(lumi)} $   $\text {\,pb}$ . The normalized differential cross sections are measured as a function of the top quark transverse momenta, $p_{\mathrm {T}}$ , and compared to predictions from quantum chromodynamics. The results are reported at detector, parton, and particle levels. In all cases, the measured top quark $p_{\mathrm {T}}$ spectra are significantly softer than theoretical predictions.